ANALYSIS OF SHORT STORY “THE TELL-TALE HEART” BY EDGAR ALLAN POE: INDICATIONS FOR STYLISTICS TEACHING. - Arif Firmansyah (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This essay uses style analysis as a tool to examine the narrator's internal and external worlds in the short story "The Tell-Tale Heart." Here, stylistic analysis is essential because it clarifies how language and creative expression are related. The story's structure is highlighted in particular, as it makes use of devices like parallelism and the transitory quality of processes—both material and mental—to highlight the narrator's strange actions and compulsive obsession with the elderly man's "vulture's eye." The narrator's actions, which are characterized by careful planning and cunning maneuvers, highlight his unstable mentality and contradictory treatment of the elderly guy, whom he eventually sees as a victim because of his obsession with the eye. Readers can identify the narrator's underlying objectives and motives by closely analyzing that speech served and utterances that make up his story. This analysis aims to clarify the ways in which the narrator's journey into illness and obsession is portrayed through stylistic decisions in character development, dialogue, imagery, point of view, theme, and tone.